The Ettingshausen effect in doped semiconductor superlattice under the influence of confined optical phonon - Thi Lam Quynh, Nguyen; Ba, Cao Thi Vi; Quang Bau, Nguyen (VNU Journal of Science: Mathematics - Physics, 2020)
The electron – optical phonon scattering is considered in detail to studying the Ettingshausen effect in doped semiconductor superlattice under the influence of phonon confinement and laser radiation. The analytical expressions for tensors and the Ettingshausen coefficient are obtained by using the kinetic equation method. The Ettingshausen coefficient depends on temperature of the sample, amplitude and frequency of laser radiation, magnetic field and the quantum number m specific for the confinement of phonon. The dependences are clearly displayed in the numerical results for GaAs:Be/GaAs:Si doped semiconductor superlattice. The magnetic field makes the Ettingshausen coefficient change in quantitative under the influence of temperature or laser amplitude and change the resonance condition. The numerical results show that both resonance condition and resonance peaks position are affected by the increase of quantum number m. We also get the result corresponding to the unconfined optical phonon case when m is set to zero. Due to the change of the wave function and energy spectrum of electrons, most of results for the Ettingshausen effect in doped semiconductor superlattice obtained are different from the case of bulk semiconductor. Moreover, in comparison with the case of unconfined optical phonon, under the influence of phonon confinement effect, the Ettingshausen coefficient changes in magnitude, the number and position of resonance peaks.